The Polymorphism and Expression of CYP2E1 Gene and Its Relation to Carcass and Meat Quality of Indonesian Lamb - R. S. Harahap; R. R. Noor; A. Gunawan (Faculty of Animal Science, Bogor Agricultural University, 2021)
The aim of this study was to conduct the genotyping of the single nucleotide polymorphism (SNP) in g.50657948 T>G of the CYP2E1 gene and its relation to the carcass and meat quality. A total of 200 Indonesian lambs consisted of 20 Javanese fat-tail sheep (JFTS), 37 Javanese thin-tail sheep (JTTS), 20 Garut sheep (GS), 21 Jonggol sheep (JS), 34 Garut composite sheep (GCS), 35 compass agrinac sheep (CAS), and 33 Barbados cross sheep (BCS) aged between 10-12 months old were used in this study. The polymorphism of the CYP2E1 gene was characterized using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) with NlaIII enzyme restriction. The CYP2E1 gene found the three genotypes (GG, GT, and TT) and the allele frequencies were in Hardy Weinberg equilibrium. The CYP2E1 gene was significantly associated with meat quality, i.e., pH value and tenderness, as well as fatty acid composition (p<0.05), i.e., saturated fatty acid (SFA): caprylic acid (C8:0), arachidic acid (C20:0), heneicosylic acid (C21:0), behenic acid (C:22:0), and tricosylic acid (C23:0), monounsaturated fatty acid (MUFA): elaidic acid (C18:1n9t) and paullinic acid (C20:1); polyunsaturated fatty acid (PUFA): linoleic acid (C18:2n6c) and y-linolenic acid (C20:3n6). A gene expression analysis indicated that the GG genotype had the highest expression level. It could be concluded that the SNP g.50657948 T>G of the CYP2E1 gene could be used for candidate marker-assisted selection to improve the carcass and meat quality of Indonesian lamb.